Factors Related to Blood Sugar Control among Diabetes Type 2 Patients, Kohyaochaipat Hospital, Kohyao District, Phangnga Province - พูลสงวน มนฑิต (Journal of Health Science of Thailand, 2022)
The objective of this study was to assess the relationship between factors related to the control of HbA1C of patients with type 2 diabetes who were treated at Kohyaochaipat Hospital by collecting data from the history file electronic medical record between October 2020 and March 2021. The samples were selected purposively based onn their willingness to participate in the study, and were divided into two groups: one with good glycemic control HbA1C <7 and the other with uncontrolled glycemic HbA1C>7. The data used in the study consisted of general information of the patient, factors related to glycemic control include duration of disease, body mass index, BMI, blood lipid levels. blood pressure level, and microalbuminuria. The data were analyzed by using descriptive statistics; and the association was calculated using binary logistic regression. It was found that there were altogether 297 patients recruited; and the factors found to be significantly associated with better glycemic control were body mass index >22, duration of diabetes >10 years, TG >150, HDL >40 (p<0.05). The results of this study may be useful to improve diabetic care with the aim to improve control of the patient’s blood sugar levels.